Implementation of Character Education from Parents in Overcoming the Danger of Drugs in Labuhanbatu District - Mulkan Darajat; Galih Orlando; Hamna Sari Siregar; Naimah Agustina; Leli Hasanah Lubis (Edumaspul: Jurnal Pendidikan, 2024)
This research discusses the implementation of character education from parents in preventing the dangers of drugs in Labuhanbatu Regency. This research was conducted using a qualitative method with a phenomenological approach. Research informants consisted of parents, teenagers and community leaders in Labuhanbatu Regency. The results of the research show that the implementation of character education from parents in Labuhanbatu Regency is quite effective in preventing the dangers of drugs. This is proven by several findings, namely: a. Children who have good character education are more protected from the dangers of drugs. b. Parents who implement character education well have stronger relationships with their children. c. The community in Labuhanbatu Regency supports the implementation of character education. The conclusion of this research is that the implementation of character education from parents is an effective effort to ward off the dangers of drugs in Labuhanbatu Regency. By providing good character education, parents can help their children become a drug-free and high-achieving generation.